Understanding Adaptive Capacity: Sustainable Livelihoods and Food Security in Coastal Bangladesh - Wright, H; Kristjanson, Patricia M.; Bhatta, Gopal Datt (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
This paper analyses data from a household-level survey of 980 agricultural and fishing households in seven sites across southern Bangladesh. We examine the relationship between assets, livelihood strategies, food security and farming practice changes. These households are coping with huge demographic, economic, and environmental changes. The results suggest that the least food secure households are also the least adaptive, and are making few, if any changes, in their agricultural practices. They have relatively few assets, and are producing and selling fewer types of agricultural products than more food secure households. The importance of diversification as a strategy to deal with change is evident - households making more farming practice changes are more diversified in terms of the number of different agricultural outputs produced and sold. Market-related factors are more frequently given as reasons for changes in practices than climate-related factors. We also see a strong relationship between education and adaptability. Households with more educated members are likelier to be introducing new agricultural practices. The often unrecognized, but important role that women play in agricultural production and livelihood strategies in Bangladesh is also evident. This rich dataset (freely available at: www.ccafs.cgiar.org/resources/baseline-surveys) provides insights into the relationship between household food security and the agricultural livelihood changes being made by rural households in southern Bangladesh. The analysis provides relatively rare empirical evidence supporting the use of the Sustainable Livelihoods Framework (SLF) as a conceptual approach for understanding household food security as well as adaptation of agriculture to climate change. This information is critical and timely for ongoing dialogues on appropriate ‘climate-resilient’ strategies and policies for increasing the adaptive capacity of households under climate change, and enhancing food security at both household and national levels.